2012
DOI: 10.5812/asjsm.34719
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sleep Deprivation on Choice Reaction Time and Anaerobic Power of College Student Athletes

Abstract: Purpose: The aim of this study was to determine the effect of one night's sleep deprivation on anaerobic performance and Reaction time of subjects in the morning of the following day.Methods: Eighteen male college student athletes were studied twice in a balanced, randomized design. Subjects were measured for peak power, mean power and Reaction time. Results:The performance showed no significant difference in both tests of anaerobic power (peak power, mean power) over the sleep deprivation period (P= 0.3; P= 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 20 publications
6
84
1
6
Order By: Relevance
“…Because of this, the potential benefits of 5-HES on cognitive performance may have been negated. The detrimental effects of sleep deprivation on cognitive performance are substantially documented [28][29][30][31]. For example, in the study by Taheri and Arabameri [29], one night of complete sleep deprivation, resulted in decreased time to task failure and cognitive performance compared with the control condition.…”
Section: Cognitive Influence Of 5-hour Energy® Drink 10mentioning
confidence: 99%
“…Because of this, the potential benefits of 5-HES on cognitive performance may have been negated. The detrimental effects of sleep deprivation on cognitive performance are substantially documented [28][29][30][31]. For example, in the study by Taheri and Arabameri [29], one night of complete sleep deprivation, resulted in decreased time to task failure and cognitive performance compared with the control condition.…”
Section: Cognitive Influence Of 5-hour Energy® Drink 10mentioning
confidence: 99%
“…Restoration of RT is important following concussion as it serves as a protective mechanism and effects performance. 6 Therefore, identifying a reliable means of objectively quantifying RT may aid in improving return to participation decision making.…”
Section: Abstract: Testing and Measurement Clinical-evaluation Evalmentioning
confidence: 99%
“…Restoration of RT is important following concussion as it serves as a protective mechanism and effects performance. 6 Therefore, identifying a reliable means of objectively quantifying RT may aid in improving return to participation decision making.The Dynavision D2® (Dynavision; Dynavision International LLC, West Chester, OH) light board provides an objective measure to assess RT and visuomotor response. This device is equipped with customizable protocols capable of measuring and training RT.…”
mentioning
confidence: 99%
“…[6] Earlier many studies were done to assess the effect of sleep deprivation and shift work on reaction time. [1,8] Only one study showed the effect of rotating shift work on VEP. [1,9] Hence, with the aim of adding more evidence regarding the change in VEP due to the disturbance of circadian rhythm among rotating shift workers, this study was planned.…”
Section: Introductionmentioning
confidence: 99%